Occurrence, Antimicrobial Resistance Pattern and Plasmid Profile of Salmonella spp. Isolated from Raw Beef Meat in Dhaka City - Azad, Abul Kalam; Parveen, Sahana; Ahmed, Md Shakir Uddin; Malek, Md Abdul (Bangladesh Journal of Microbiology, 2016)
Salmonella is motile enterobacterium that causes diseases like typhoid fever, paratyphoid fever and food borne illnesses. Salmonella infections are due to the consumption of contaminated foods. The objective of the present study was to observe the sanitary and hygienic conditions of the retail areas and to isolate pathogenic Salmonella spp from raw beef, to observe antimicrobial sensitivity pattern of Salmonella spp from the raw beef. A total of forty (40) raw beef samples were collected from the sixteen different butcher shops of the four different markets namely Bazaar-1, Bazaar-2, Bazaar-3 and Bazaar-4 of Dhaka City to determine the presence of the significant enteric pathogen Salmonella. From the colony characteristic and biochemical properties, it was found that out of forty samples Salmonella were found in thirty four (85%) samples. The prevalence of drug resistance bacteria were also assayed by antibiotic susceptibility testing. Among thirty four isolates, nearly 6% (2), 32% (11), 76% (26), 6%(2) and 32% (12) isolates showed resistance to Nitrofurantoin, Nalidixic acid, Ampicillin , Gentamycin and Trimethoprim-sulfamethoxazole respectively. Almost 85%(29), 62%(21), 24% (8), 91% (31), 91% (31)and 68% (23) isolates showed sensitivity to Nitrofurantoin, Nalidixic acid, Ampicillin,Ciprofloxacin,Gentamycin and Trimethoprim-sulfamethoxazole respectively Some isolates also showed intermediate in sensitivity reaction for example 3% (1), 6% (2), 3% (1) and 9% (3) isolates showed intermediate in sensitivity reaction to Nitrofurantoin, Ampicillin, Ciprofloxacin, Gentamycin and Nitrofurantoin respectively. Twenty four isolates were investigated for the plasmid profile analysis where thirteen isolates (about 54%) were found to carry plasmids of different sizes ranging from small (2.3 kb) to large sizes (>10kb and also greater than the chromosomal DNA). The presence of large plasmids may be a possible source of drug resistance. The results of this study demonstrate the unhygienic quality of beef meat and their risk of contracting food borne infections to the consumers. Bangladesh J Microbiol, Volume 29, Number 1, June 2012, pp 17-22